Development of Bali Cattle in Smallholder Farm Based on Population Structure in Maiwa Enrekang Regency - Muhammad Farid Abbas; Sudirman Baco; Muhammad Hatta (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2022)
Abstract This study was conducted to determine the improvement of the Bali cattle population in smallholder farms based on the structure of population. This research was carried out from September to November 2019 at the Maiwa Breeding Center Partnership, Enrekang Regency. The type of research used was descriptive research, which we study that describes the variable condition, that are birth rates, mortality, sales, purchases, and population structure at the smallholder farm. The first stage was to collect data by direct observation in the field. The second stage was to carry out tabulation and data analysis. The results of the research were that the increased of Bali cattle at the Maiwa smallholder farm partnership in Maiwa Breeding Center in Enrekang Regency was influenced by calving rate of cows. The calving rate was founded was 23% in 2017, 32% in 2018, and 46% in 2019, respectively. The mortality rate and sales of cattle was 6%in 2017, 4% in 2018 and 17% in 2019, respectively. The population dynamics was affected by calving rate, mortality and sales livestock in a year. Prediction of population growth increased gradually (7% a year) from 2020 to 2025 based on the population structure of Smallholder Farm in 2019. It is expected that the calving rate is at least 60% in a year. Keywords : Population dynamics, calving rate, mortality rate, birth rate, population growth